2016
DOI: 10.1097/md.0000000000005120
|View full text |Cite
|
Sign up to set email alerts
|

Association of the KLK1 rs5516 G allele and the ACE D allele with aortic aneurysm and atherosclerotic stenosis

Abstract: Objective:Atherosclerosis underlies aortic aneurysm (AA) and atherosclerotic stenosis (AS). Kallikrein-1 (KLK1) and angiotensin-converting enzyme (ACE) are 2 key molecules in kallikrein-kinin systems and renin-angiotensin systems, respectively, which are responsible for maintaining vascular balance and stability, playing important roles in atherosclerosis. We aimed to assess the involvement of single nucleotide polymorphism rs5516 in KLK1 as well as the insertion/deletion rs4646994 polymorphism in ACE in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Here, we identified SNP rs5516, a stop-gained mutation for KLK1 (Kallikrein 1), with the highest pathogenicity score and a significantly high frequency in AAA (17.8%). Indeed, previous SNPs studies performed in both Australian and Asian cohorts have shown the association of rs5516 with AAA 30,43 . Our analysis identified other interesting polymorphism profiles associated with significant genes that correlated with AAA.…”
Section: Discussionmentioning
confidence: 95%
“…Here, we identified SNP rs5516, a stop-gained mutation for KLK1 (Kallikrein 1), with the highest pathogenicity score and a significantly high frequency in AAA (17.8%). Indeed, previous SNPs studies performed in both Australian and Asian cohorts have shown the association of rs5516 with AAA 30,43 . Our analysis identified other interesting polymorphism profiles associated with significant genes that correlated with AAA.…”
Section: Discussionmentioning
confidence: 95%
“…Here, we identi ed SNPs rs5516, which is a stop-gained mutation for KLK1, had the highest pathogenicity score with a signi cantly high frequency in AAA (17.8%). Indeed, previous SNPs study had shown its association in aortic aneurysm with evidence pointing out the role of KLK1 with proin ammatory and vascular remodeling properties of the aorta 29 . Our analysis identi ed other interesting polymorphism pro les associated with signi cant genes correlated with AAA.…”
Section: Discussionmentioning
confidence: 97%
“…The SNP rs5516, which codes for KLK1 is a stop-gained mutation. The CG allele of this SNP is 17.8% more expressed in Australian AAA patients than in control groups 29 . The SNP rs1801133, coding for MTHFR is a nonsynonymous mutation, its CT/CC allele is only 3% more expressed in Greek AAA patients than in control 30 .…”
Section: Tablementioning
confidence: 87%